Aproveitamento de biogás e lodo excedente de reatores UASB como fonte de energia renovável em estações de tratamento de esgoto - André Pereira Rosa (2013)
The research aimed to evaluate the recovery of by-products biogas and excess sludge in UASB reactors as renewable energy in wastewater treatment plants (WWTP). The objective 1 was developed after an extensive literature review and visits to European WWTP that have energetic recovery. In the ambit of objective 2, the work was developed at Laboreaux STP, Itabira-MG through the energetic potential characterization of sludge and biogas and proposal of mass and energy balance, besides the calculation of greenhouse gases reduction for two scenarios (i): priority use of biogas for sludge thermal drying and the excess of biogas being used for power generation in an internal combustion engine (ICE); and (ii) primary use of biogas for power generation and the heat of the engine exhaustion gases being used for sludge thermal drying. Finally, the last objective proposed a mathematical model to estimate the energetic balance in WWTP by the use of by-products in anaerobic treatment as source of energy. Among main results could be concluded that sludge has technical and environmental feasibility as source of energy, beyond its joint use with biogas from UASB reactors. In addition, thermo-chemical processes (pyrolysis, gasification and combustion) are potentially alternatives with many benefits mainly for large size WWTP that have high costs of transportation and final destination. In addition the energetic sludge recovery in a individual manner or even in association with other by-products from WWTP as biogas could guarantee sludge own drying and permit development and increasing of thermal processes for brazilian reality. For Laboreaux STP it was verified that the energetic potential for biogas and sludge from UASB reactors were 10,962 MJ.d-1 and 7,518 MJ.d-1, respectively. The electricity supply was 22.2% and 57.6 % for scenarios (i) and (ii), respectively. The scenario (i) stood out in sludge sending for landfill, while scenario (ii) presented high energetic potential for electricity generation for benefit of WWTP. For scenario (i) the credit carbon reduction with sludge recovery sent until now to landfill (1,372 t.year-1 and 10% of moisture) was 12,691 t.CO2.e. Concerning the mathematical model development, the results indicated the possibility of a realistic estimative of sludge production and total energetic potential in WWTP.